Correction: Interaction mechanism between a functionalized protective layer and dissolved polysulfide for extended cycle life of lithium sulfur batteries. Issue 28 (28th July 2015) - Ahn, Wook; Lim, Sung Nam; Lee, Dong Un; Kim, Kwang-Bum; Chen, Zhongwei; Yeon, Sun-Hwa; Jin, Chang-Soo
<x xml:space="preserve">Abstract</x> Correction for 'Interaction mechanism between a functionalized protective layer and dissolved polysulfide for extended cycle life of lithium sulfur batteries' by Wook Ahn et al., J. Mater. Chem. A, 2015, 3, 9461–9467.